The effect of service quality, brand image, price perception and innovation on consumer trust (study on Honda motorcycle users in Kudus Regency) - Dina Lusianti; Feby Dwi Fitriya; Keke Tamara Fahira (Business, Accounting, and Knowledge Journal, 2026)
This research is intended to examine the effect of service quality, brand image, price perception, and innovation on consumer trust among users of Honda PCX motorcycles in Kudus Regency. The study population consisted of consumers who had purchased and used the motorcycle within the last six months. A total of 150 respondents were selected through a purposive sampling method. The collected data were processed and analyzed using multiple linear regression analysis. The findings indicate that service quality exerts a positive and significant impact on consumer trust. Likewise, brand image has a positive and significant effect on consumer trust. In addition, price perception positively and significantly influences consumer trust. Innovation also demonstrates a positive and significant effect on consumer trust. Collectively, service quality, brand image, price perception, and innovation simultaneously have a positive and significant influence on consumer trust.